2008
DOI: 10.1111/j.1530-0277.2008.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 5α‐Reduced Steroid Biosynthesis Impedes Acquisition of Ethanol Drinking in Male C57BL/6J Mice

Abstract: Background-Allopregnanolone (ALLO) is a physiologically-relevant neurosteroid modulator of GABA A receptors, and it exhibits a psychopharmacological profile that closely resembles the postingestive effects of ethanol. The 5α-reductase inhibitor finasteride (FIN), which inhibits biosynthesis of ALLO and structurally-related neurosteroids, was previously demonstrated to reduce the maintenance of limited-access ethanol consumption. The primary aim of the current work was to determine whether FIN would reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 22 publications
(45 reference statements)
5
51
0
Order By: Relevance
“…85 Mr Q currently takes finasteride and zolpidem. Finasteride reduces alcohol intake in mice 86 but is unlikely to interact meaningfully with alcohol. Zolpidem and alcohol produce additive levels of sedation that could interfere with activities occurring after the time of dosing and could produce excessive morning sedation, but risk is unlikely if zolpidem dosing occurs just before bed and 1 or 2 drinks are taken with dinner.…”
Section: Endogenous Sex Steroid Hormonesmentioning
confidence: 99%
“…85 Mr Q currently takes finasteride and zolpidem. Finasteride reduces alcohol intake in mice 86 but is unlikely to interact meaningfully with alcohol. Zolpidem and alcohol produce additive levels of sedation that could interfere with activities occurring after the time of dosing and could produce excessive morning sedation, but risk is unlikely if zolpidem dosing occurs just before bed and 1 or 2 drinks are taken with dinner.…”
Section: Endogenous Sex Steroid Hormonesmentioning
confidence: 99%
“…Indeed, to our knowledge, the effects of finasteride have so far generally been explored after the administration of very high doses [2,8,9,10,11,12,13,14,15,16,17,18]. We demonstrated that, in agreement with the well-known effect of finasteride in the prostate [35], a significant decrease in its relative weight was observed at the end of the subchronic treatment with the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the metabolites of PROG and T are involved in the regulation of neuroendocrine events, behavior, affection, learning and memory, synaptic and glial plasticity and adult hippocampal neurogenesis as well as in the response of brain tissue to injury and neurodegeneration (i.e., regulating neuronal survival, axonal regeneration and gliosis) [1,5,6,7]. Finasteride has been used as a tool to evaluate whether the effects of PROG or T in the nervous tissue could be ascribed to their conversion into 5α-reduced metabolites [2,8,9,10,11,12,13,14,15,16,17,18]. However, despite of the wide therapeutic use of this inhibitor (e.g., human benign prostatic hyperplasia and androgenic alopecia), the effects of finasteride per se in the nervous system have been poorly explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, others and we have shown that restricted access to ethanol for 2-4 h/day in a two-bottle setup, where mice have the choice between water and ethanol, results in high preference for ethanol [20,21]. Although preference for the ethanol solution often does not exceed 50% for C57BL/6J mice in a 24-h two-bottle choice paradigm [4,6], in the limited access paradigm C57Bl/6J mice drink more than 2 g/kg ethanol in 2-4 h sessions with a preference exceeding 80% [20,21].…”
Section: Introductionmentioning
confidence: 95%